Aplicaciones pedagógicas de la marmita de frutas de 50 litros en procesos de transformación agroindustriales. - Granda Delgado, Katherine Nicole (2022)
The present work on "Pedagogical applications of 50-liter fruit pot for agro-industrial transformation processes" mentions the use of the equipment found in fruit and vegetable laboratories of Technical University of Cotopaxi, which allows to Agroindustry students could make correct use of it, on new knowledge generation and research. because products that are made in pot are safe, innocuous and high quality, the pot has a stainless steel structure 304 quality, also has a capacity of 50 liters, a tipping design and it is easy to maintain with a 220 V requirement, it has an adjustable temperature control system that allows necessary heating and cooling for cooking and pasteurization of different products. In the present work, the bibliographical research is used for manuals elaboration, where main parts of the pot and its correct function are specified, besides operating mechanism is divided into three important points. such as, steam production, rapid cooking and pressure build-up. The maintenance manual was elaborated with procedures and frequency types maintenance that must be carried out on kettle that are specified, such as: routine, preventive, predictive and corrective. Next, a personnel safety prevention guide was carried out. Afterwards, it was possible to execute practical application of the pot, in which different products such as tomato sauce, Pickles and chocolate milk were developed. At the end of the manual you will find different types of operating and maintenance records for the kettle.